2011
DOI: 10.1038/ni.2051
|View full text |Cite
|
Sign up to set email alerts
|

A semi-invariant Vα10+ T cell antigen receptor defines a population of natural killer T cells with distinct glycolipid antigen–recognition properties

Abstract: Type I natural killer T cells (NKT cells) are characterized by an invariant variable region 14–joining region 18 (Vα14-Vα18) T cell antigen receptor (TCR) α-chain and recognition of the glycolipid α-galactosylceramide (α-GalCer) restricted to the antigen-presenting molecule CD1d. Here we describe a population of α-GalCer-reactive NKT cells that expressed a canonical Vα10-Jα50 TCR α-chain, which showed a preference for α-glucosylceramide (α-GlcCer) and bacterial α-glucuronic acid–containing glycolipid antigens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
127
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 50 publications
(80 reference statements)
11
127
1
Order By: Relevance
“…Consequently, our data suggest that the Vα chain and specifically, the Jα18-encoded loop, which contacts CD1d and the Ag, drive the pattern recognition receptor properties of the NKT TCR (26). However, recent studies have also identified a population of α-GalCer-reactive semi-invariant NKT cells in which the TCR α-chain is comprised of the Vα10-Jα50 genes and the TCR β-chain is largely restricted to the Vβ8 and Vβ7 genes (23). Despite the markedly different sequences of the Jα18-and Jα50-encoded gene segments, the Vα10-Jα50 NKT TCR docked onto CD1d-Ag in a very similar manner to the docking of the Vα14-Jα18 NKT TCR-CD1d-Ag complexes.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Consequently, our data suggest that the Vα chain and specifically, the Jα18-encoded loop, which contacts CD1d and the Ag, drive the pattern recognition receptor properties of the NKT TCR (26). However, recent studies have also identified a population of α-GalCer-reactive semi-invariant NKT cells in which the TCR α-chain is comprised of the Vα10-Jα50 genes and the TCR β-chain is largely restricted to the Vβ8 and Vβ7 genes (23). Despite the markedly different sequences of the Jα18-and Jα50-encoded gene segments, the Vα10-Jα50 NKT TCR docked onto CD1d-Ag in a very similar manner to the docking of the Vα14-Jα18 NKT TCR-CD1d-Ag complexes.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the structures of NKT TCRs in complex with α-GalCer analogs as well as α-galactosyldiacylglycerol, the self-Ag phosphatidyl inositol, and some β-linked Ags have been determined (17)(18)(19)(20)(21)(22)(23). In all NKT TCR-CD1d-Ag complexes determined to date, a conserved, tilted, and parallel docking mode with respect to the CD1d Agbinding cleft was observed.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Although there is some hierarchy in affinity of different mouse iNKT cell TCRs based on TCR β-chain use (22,23), stimulation with iNKT cell antigens generally results in immediate, innate-like responses of the entire iNKT cell population. iNKT cells, and the recently described semi-invariant Vα10 + CD1d-restricted NKT cells, use a unique mode of TCR recognition of lipid/CD1d complexes in which recognition of the lipid antigen is mediated primarily by the semi-invariant TCR α-chain, and the TCR β-chain appears to only modulate affinity (24)(25)(26). In contrast, MHC-restricted T cells, as well as human CD1a-, b-, and c-restricted T cells, show a high degree of specificity for unique antigens and stimulation with their cognate antigens results in clonal expansion and adaptive T-cell responses (27).…”
Section: Very Strong;mentioning
confidence: 99%